Champion school: A year to year model to developing elite athletes - Bondarchuk, A. P. (Ultimate Athlete Concepts, 2015)
Dr. Anatoly Bondarchuk is renowned as an athlete (1972 Olympic Champion and European Champion in the hammer throw as well as a former World Record holder) and Mr. Bondarchuk's coaching credentials are virtually unprecedented in the sport of athletics. Dr. Bondarchuk is a Doctor of Pedagogical Science ( University of Kiev ) and his research into technique and high-performance training methods formed the basis for many of the common techniques and practices used by the world's top athletes today. In this book "Champion School: A Year to Year Model To Developing Elite Athletes", Dr. Bondarchuk goes into great explaination of the long-term process of developing an athlete, the essentials of constructing a system of sports improvement based on an athletes age, how and when to develop physical qualities, methods of constructing sports form and means for distrubuting volume and intensity of traininly loads over the yearly and multi-yearly training cycles. (Verlagsinformation)